HEAT KILLED PROBIOTIC LACTOBACILLUS PLANTARUM INDUCES NF KAPPA B FACTOR COMPARED WITH LIVE BACTERIA AND LIPOPOLYSACCHARIDES ON HEK – 293 CELL LINES - PRATHIBA SANDEEP; P. SARAVANA KUMARI (International Journal of Pharma and Bio Sciences, 2016)
Probiotics are live microorganisms which have shown beneficial effects on human health.1 Conditions susceptible to treatment with probiotics include traveler’s, antibiotic-induced, and childhood diarrhea. Recently, several controlled clinical studies have also proven a role for probiotic therapy in different states of inflammatory bowel diseases.The aim of our study was to compare Heat killed probiotic bacterial strain of Lactobacillus plantarum with live bacteria with respect to innate defense mechanisms in the HEK-293 cells. Here we report L.plantarum tested to induce the NF -κB activation or expression in HEK 293 cell lines in a time - and dose-dependent manner. Activation of NF -κB through Heat killed bacteria was confirmed by fold change in HEK-293 cell lines. Luciferase gene reporter analyses assay experiments demonstrated that NF -κB activation is seen in HEK-293 cell lines through Heat killed cells of L.plantarum. This report demonstrates that Heat killed probiotic bacteria, L.plantarum can stimulate the immune cells by induction of NF –κB.